2020
DOI: 10.3390/cancers12102907
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 Deficiency Reduces Tumour Growth by Decreasing E2F1 Hyperactivation: A Novel Mechanism in the Treatment of Cancer

Abstract: In recent years, poly (ADP-ribose) polymerase (PARP) inhibitors have been evaluated for treating homologous recombination-deficient tumours, taking advantage of synthetic lethality. However, increasing evidence indicates that PARP1 exert several cellular functions unrelated with their role on DNA repair, including function as a co-activator of transcription through protein-protein interaction with E2F1. Since the RB/E2F1 pathway is among the most frequently mutated in many tumour types, we investigated whether… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
7
10
0
Order By: Relevance
“…Once released from arrest, cells were treated with the different inhibitors, as shown in Figure 2C. The enzymatic inhibition of PARP1 reduced the transcriptional activity of E2F1 in a manner similar to that of the PARP1 deficiency that we previously reported [9]. Within the experimental groups, we found that PJ34 is possibly the molecule, among the classical inhibitors of PARP1, that reduces this transactivation to a greater extent, while the luciferase activity is reduced by almost 40% compared with the untreated control in cells treated with gossypol.…”
Section: In Vitro Effect Of Parp Inhibitors On the Interaction Of Par...supporting
confidence: 64%
See 3 more Smart Citations
“…Once released from arrest, cells were treated with the different inhibitors, as shown in Figure 2C. The enzymatic inhibition of PARP1 reduced the transcriptional activity of E2F1 in a manner similar to that of the PARP1 deficiency that we previously reported [9]. Within the experimental groups, we found that PJ34 is possibly the molecule, among the classical inhibitors of PARP1, that reduces this transactivation to a greater extent, while the luciferase activity is reduced by almost 40% compared with the untreated control in cells treated with gossypol.…”
Section: In Vitro Effect Of Parp Inhibitors On the Interaction Of Par...supporting
confidence: 64%
“…As we have already shown [9], Parp1 +/+ cRb -/-HRas V12 astrocytes obtained from P3 neonates present great heterogeneity in their shape and size, together with several morphological alterations, such as the presence of abundant cytoplasmic extensions. Loss of contact inhibition and formation of growth foci in the culture plates, which reflect the existence of a transformed phenotype, was also observed in these cells.…”
Section: Chemical Inhibition Of Parp1/e2f1 Interaction In a Model Of ...mentioning
confidence: 64%
See 2 more Smart Citations
“…Recently PARP-inhibitors have been approved for therapy in PCa patients with DDR pathway mutations and have already been used to treat t-NEPC patients with such aberrations, though only with limited success [ 129 ]. PARP1 is a chromatin associated enzyme modifying various nuclear proteins by poly-ADP-ribosylation, but it also functions as transcriptional coactivator for E2F1 [ 130 ]. In t-NEPC cell models and xenografts, PARP inhibitors have been shown to decrease cell proliferation and tumor growth.…”
Section: Mechanisms Of T-nepc Developmentmentioning
confidence: 99%